Trends in data literacy, 2018-2023: a review of the literature - Bowler, Leanne; Shaw, Charlie (Information Research an international electronic journal, 2024)
Introduction. A review of the literature on data literacy from 2018 to mid-2023. Method. A scoping review of the data literacy literature, in order to provide an overview of a topic, clarify key concepts, and identifying knowledge gaps. Analysis. A detailed search strategy was applied to three data bases: SCOPUS, the ACM Digital Library, and the IEEE Xplore, followed by a qualitative analysis using a coding matrix of eight categories. Results. Trends and gaps in the research were identified. The volume of research on data literacy is growing. Most data literacy research is in the context of formal learning environments. The focus of data literacy tends to be on digital data, interactions with big data systems, and the datafication of life. Critical data literacy approaches were identified in one third of the sample papers - a small but emerging stance to data literacy education. Most empirical studies about data literacy occurred in the Global North. Conclusion. This paper contributes to our understanding of how data and data literacy are currently interpreted in the research literature, as well as the types of topics, skills, and data practices explored. It reveals developing trajectories and proposes future steps for building out the field of data literacy.